STRATEGI KEPALA SEKOLAH UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM MENGHADAPI UN DI SMP NEGERI 4 YOGYAKARTA - Faizah Faizah; Ahmad Fauzan (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2019)
The purpose of this study is to know the strategy of the head master of SMP Negeri 4 Yogyakarta in order to increase student motivation in facing the National Examination (UN) after two years of decline. Using a qualitative descriptive method this study aims to describe the form of the principal's strategy, supporting and inhibiting factors and implications. The form of the principal's strategy, including: (1) collaboration with guardians of students, teachers and principals; (2) motivational training activities; (3) learning innovations; (4) become leaders, supervisors and managers; and (5) encourage students to have learning reference books. Supporting and inhibiting factors come from principals, teachers, students, guardians of students and the environment. The results of the school principal's implications, namely: (1) the motivation of students to follow tutoring increases, (2) students become active in the classroom, (3) student learning motivation increases; and (4) UN results are better than the previous year. Key words: principal's strategy, students learning motivation, national examination.